Racial Disparities in Postoperative Outcomes Following Operative Management of Pediatric Developmental Dysplasia of the Hip. Issue 5 (24th May 2022) - Malyavko, Alisa; Quan, Theodore; Howard, Peter G.; Recarey, Melina; Manzi, Joseph E.; Tabaie, Sean
Abstract : Background: Developmental dysplasia of the hip in pediatric patients can be managed conservatively or operatively. Understanding patient risk factors is important to optimize outcomes following surgical treatment of developmental dysplasia of the hip. Racial disparities in procedural outcomes have been studied, however, there is scarce literature on an association between race and complications following pediatric orthopaedic surgery. Our study aimed to determine the association between pediatric patients' race and outcomes following operative management of hip dysplasia by investigating 30-day postoperative complications and length of hospital stay. Methods: The National Surgical Quality Improvement Program-Pediatric database was utilized from the years 2012 to 2019 to identify all pediatric patients undergoing surgical treatment for hip dysplasia. Patients were stratified into 2 groups: patients who were White and patients from underrepresented minority (URM) groups. URM groups included those who were Black or African American, Hispanic, Native American or Alaskan, and Native Hawaiian or Pacific Islander. Differences in patient demographics, comorbidities, and postoperative outcomes were compared between the 2 cohorts using bivariate and multivariate analyses. Results: Of the 9159 pediatric patients who underwent surgical treatment for hip dysplasia between 2012 and 2019, 6057 patients (66.1%) were White and 3102 (33.9%) were from URM groups. In the bivariate analysis, compared with White patients, patients from URM groups were more likely to experience deep wound dehiscence, pneumonia, unplanned reintubation, cardiac arrest, and extended length of hospital stay. Following multivariate analysis, patients from URM groups had an increased risk of unplanned reintubation (odds ratio: 3.583; P =0.018). Conclusions: Understanding which patient factors impact surgical outcomes allows health care teams to be more aware of at-risk patient groups. Our study found that pediatric patients from URM groups who underwent surgery for correction of hip dysplasia had greater odds of unplanned reintubation when compared with patients who were White. Further research should investigate the relationship between multiple variables including race, low socioeconomic status, and language barriers on surgical outcomes following pediatric orthopaedic procedures. Level of Evidence: Level III—retrospective cohort analysis.